Influence of Gold Nanoparticle Film Porosity on the Chemiresistive Sensing Performance. Issue 10 (18th September 2013) - Chow, Edith; Raguse, Burkhard; Müller, Karl‐H.; Wieczorek, Lech; Bendavid, Avi; Cooper, James S.; Hubble, Lee J.; Webster, Melissa S.
Abstract The porosity of 1‐hexanethiol‐functionalised gold nanoparticle films was assessed and utilised as chemiresistor sensors. Electrochemical capacitance measurements showed that the accessibility of electrolytes of different ionic strengths into the pores depended on the thickness of the electric double layer formed. A large variation in capacitance was measured in 0.01–1000 mM NaClO4, implying a wide pore size distribution. The change in morphology of the nanoparticle films upon storage in air, water and ethanol for two weeks was investigated. There was a significant decrease in the electrochemical capacitance at high electrolyte concentrations for the ethanol‐stored films compared to the freshly‐prepared films suggesting a decrease in the number of small pores of radii in the range of 0.3–3 nm. This was further supported by optical topographical measurements where a decrease in the thickness of ethanol‐stored films was observed relative to the freshly‐prepared films. The porous nature of the nanoparticle films was found to have an effect on the chemical sensing behaviour. When used as chemiresistor sensors, for the detection of heptane in water, the ethanol‐stored films provided larger resistance changes and longer response times. This suggests that the more densely packed ethanol‐stored films provided more sites that enabled film swelling, and that diffusion of the analyte occurred through the narrower water‐filled pores. This demonstrates the effect of different storage conditions on film morphology and subsequently sensor response.